Reduced well-being during the COVID-19 pandemic – The role of working conditions - Gundula Zoch; Ann-Christin Bächmann; Basha Vicari (Gender, Work & Organization, 2021)
The COVID-19 pandemic has had diverse impacts on the employment conditions and family responsibilities of men and women. Thus, women and men were exposed to very different roles and associated challenges, which may have affected their well-being very differently. Using data from the National Educational Panel Study and its supplementary COVID-19 web survey for Germany (May–June 2020), we investigate gender differences in the relationship between working conditions and within-changes in subjective well-being. We systematically consider the household context by distinguishing between adults with and without younger children in the household. The results from multivariate change-score regressions reveal a decline in all respondents' life satisfaction, particularly among women with and without younger children. However, the greater reduction in women's well-being cannot be linked to systematic differences in working conditions throughout the pandemic. Kitagawa–Oaxaca–Blinder counterfactual decompositions confirm this conclusion. Further analyses suggest that women's caregiving role, societal concerns, and greater loneliness partly explain the remaining gender differences in altered satisfaction. From a general perspective, our results suggest important gender differences in social life and psychological distress at the beginning of the pandemic, which are likely to become more pronounced as the crisis has unfolded.
Keywords: 300; coronavirus crisis; employment; gender inequalities; gender roles; NEPS-C; satisfaction